Paraben Compounds—Part I: An Overview of Their Characteristics, Detection, and Impacts - Lincho, João (2021)
Parabens are widely used in different industries as preservatives and antimicrobial compounds. The evolution of analytical techniques allowed the detection of these compounds in different sources at g/L and ng/L. Until today, parabens were already found in water sources, air, soil and even in human tissues. The impact of parabens in humans, animals and in ecosystems are a matter of discussion within the scientific community, but it is proven that parabens can act as endocrine disruptors, and some reports suggest that they are carcinogenic compounds. The presence of parabens in ecosystems is mainly related to wastewater discharges. This work gives an overview about the paraben problem, starting with their characteristics and applications. Moreover, the dangers related to their usage were addressed through the evaluation of toxicological studies over different species as well as of humans. Considering this, paraben detection in different water sources, wastewater treatment plants, humans and animals was analyzed based on literature results. A review of European legislation regarding parabens was also performed, presenting some considerations for the use of parabens.